In situ X-ray diffraction monitoring of a mechanochemical reaction reveals a unique topology metal-organic framework - Katsenis, Athanassios D.; Puškarić, Andreas; Štrukil, Vjekoslav; Mottillo, Cristina; Julien, Patrick A.; Užarević, Krunoslav; Pham, Minh-Hao; Do, Trong-On; Kimber, Simon A. J.; Lazić, Predrag; Magdysyuk, Oxana; Dinnebier, Robert E.; et al. (Nature communications, 2015)
Chemical and physical transformations by milling are attracting enormous interest for their ability to access new materials and clean reactivity, and are central to a number of core industries, from mineral processing to pharmaceutical manufacturing. While continuous mechanical stress during milling is thought to create an environment supporting nonconventional reactivity and exotic intermediates, such speculations have remained without proof. Here we use in situ , real-time powder X-ray diffraction monitoring to discover and capture a metastable, novel-topology intermediate of a mechanochemical transformation. Monitoring the mechanochemical synthesis of an archetypal metal-organic framework ZIF-8 by in situ powder X-ray diffraction reveals unexpected amorphization, and on further milling recrystallization into a non-porous material via a metastable intermediate based on a previously unreported topology, herein named katsenite ( kat ). The discovery of this phase and topology provides direct evidence that milling transformations can involve short-lived, structurally unusual phases not yet accessed by conventional chemistry. Ball milling chemical reactions are of interest due to their environmental credentials and potential to achieve new reactions and materials. Here, the authors isolate a metastable material with a previously unknown net topology by in situ monitoring of the mechanosynthesis of a metal organic framework.